Transdiagnostic internet-delivered therapy among post-secondary students: exploring student use and preferences for booster lessons post-treatment. (22nd June 2022) - Patterson, T.; Peynenburg, V.; Hadjistavropoulos, H.D.
Abstract: Internet-delivered cognitive behaviour therapy (ICBT) is effective for treating anxiety and depression among post-secondary students, although outcomes are modest. Booster lessons have been proposed for maintaining and improving outcomes but have not been investigated following ICBT for students. This study used a mixed-methods approach to examine student ( N = 146) use of a self-guided booster lesson offered 1 month after a 5-week ICBT course, whereby the booster lesson provided a review of ICBT skills and suggestions for maintaining motivation and problem solving. A survey about the booster was administered shortly after the booster to understand student preferences for the booster lessons, reasons for completing/not completing the booster, and satisfaction with the booster. Approximately one-third of students ( n = 47) utilized the booster lesson. Completing a greater number of lessons during the main ICBT course was associated with uptake of the booster. The booster survey was completed by 20 of the 47 (∼43%) students who completed the booster lesson and 42 of the 99 who did not (∼42%). Students varied in perceptions of the ideal timing of the booster (1–2 weeks to 3–6 months) and approximately 60% expressed preference for completing the booster independently. Among non-completers of the booster, academic-related time constraints were the primary barrier to booster completion. Among those who completed the booster, the booster lesson was perceived as worthwhile, satisfaction was high, and the length was perceived as appropriate. Future research should examine if flexible delivery of booster lessons in terms of timelines and therapist support would increase booster uptake. Key learning aims: As a result of reading this paper, readers should: (1) Understand the uptake of a self-guided booster lesson in internet-delivered cognitive behaviour therapy (ICBT) among post-secondary students. (2) Understand students' preferences for the content, timing, and therapist support for booster lessons. (3) Understand the need for alternative delivery methods of booster lessons to reach students who might benefit the most from a booster.